Understanding the genetic history of the Malay and Orang Asli populations in Peninsular Malaysia by killer cell immunolobulin-like receptors (KIR) - Abidin, Nur Waliyuddin Hanis Zainal (2018)
Extensive diversity of killer cell immunoglobulin-like receptor (KIR) genes among diverse populations has made these immune genes become a potential anthropological marker. The variations of KIR allotypes between two randomly selected individuals are also useful in individual identification. Here, we genotyped KIR genes content and allelic polymorphisms for the first time for Malay and Orang Asli (OA) populations in Peninsular Malaysia using polymerase chain reactionsequence specific primers (PCR-SSP), next-generation sequencing (NGS) and finally optimized by Sanger typing method. A total of 333 individuals representing 10 Malay subethnic groups (Aceh, Banjar, Bugis, Jawa, Champa, Kedah, Kelantan, Mandailing, Minangkabau and Patani) and 167 individuals from six OA subgroups (Batek, Kensiu, Lanoh, Che Wong, Semai and Orang Kanaq) have participated in this research. Fourty KIR genotypes were observed among Malays and 25 genotypes in OA populations. Generally, the Malays having homogenous haplotype profile with slightly high frequencies of haplotype A, whereas OA are heterogeneous with various genotypes and wide range of haplotypes. Based on the principal component analysis, the Malay subethnic groups are located between the Chinese, Indian and Orang Asli populations. The Semang subgroups show genetic affinity toward the Australian Aborigines, Papuan, Indian and African populations. They shared several unique genotypes (AB6, BB71, BB73 and BB159) and have high frequencies ofHaplotype B, which could be speculated as general features of ancient populations. The Senoi demonstrated high frequency of haplotype A, and expressing hybrid phenotypes between Indo-China tribes and Semang population. In contrast, Orang Kanaq, the only Proto-Malay subgroup studied is significantly different from both related Taiwanese/Chinese and neighboring Malayo-Polynesian speaking populations and show evidence of becoming a distinct population. The NGS has successfully characterized 302 different allotypes of seven studied KIR genes among Malay and OA populations. KIR2DL1, KIR2DL4, and KIR3DL3 genes show less allelic variations and in favor on particular allele, which possibly being affected by natural selection and creates selective sweep. In addition, KIR2DS4, KIR3DL1, KIR3DL2 and KIR2DL3 are highly polymorphic genes with considerable number of alleles discovered, suggesting that these genes evolved on balanced selection. The KIR3DL2 gene could be the best marker for population studies, as it comprises signature alleles (KIR3DL2*001 and *002) that support the theory of modern human migration. Comprehensive datasets generated from this research demonstrate the value of KIR genes content and allelic polymorphisms in elucidating genetic relationships between the Malays and OA with other world populations.